Operational Consequences of Private Equity Buyouts in Finland: Changes in operational efficiency and working capital investment after acquisitions - Mäkkylä, Jaska (My University, 2021)
Empirical evidence from the 1980s is constant about private equity practitioner's ability to enhance the operational profitability of their portfolio companies, while more recent findings do not show the same consistency in the results. Overall, there is a substantial amount of inconsistent evidence of the subject, and a lack of evidence about the role of working capital management behind the obtained results. This is a clear shortcoming in the earlier research, as a company can operate more efficiently by releasing capital tied up in its working capital, especially in working capital-intensive industries. This research contributes to the existing literature by analyzing the changes in operational profitability and productivity indicators of portfolio companies during the two-year post buyout period. Moreover, the research provides new evidence about the role of working capital management behind the obtained results. In Finland, the research has been led by the Finnish Venture Capital Association, which uses non-publicly available private equity databases as a source in their research. In 2013, the association began to collect a list of private equity investments from publicly available sources. This list was submitted to the author of this research, and based on this listing, the research examines 84 Finnish buyout targets and the changes in their key operational figures between the years 2014 and 2019. To explore the effect of private equity, all the figures are compared with their respective peer groups. This reveals the impact of private equity behind the obtained results and removes the erroneous conclusions that could be drawn if there is a general up- or downswing within the industry. Results show that buyout targets are growing faster in sales and employees than their peers. However, the targets are not able to maintain their operational profitability during the expansion, and the cost related to growth drive operational profitability growth to negative. Although operational profitability is not increased on average, the study finds significant improvements in working capital efficiency during the period under review. The main driver of enhanced working capital efficiency is the decrease in the receivables to sales ratio, while the research shows no evidence of increased use of trade financing or enhanced inventory turnover ratio during the reference period. Yet, the study does not find a statistical relationship between improved working capital efficiency and a firm’s operational profitability, where the main driver of abnormal operational profitability seems to be the improved employee productivity, monitored with the ratio between companywide personnel costs and sales.

Empiirinen tutkimus 1980-luvulta on osoittanut pääomasijoittajien kasvattavan sijoituksen kohteena olevien yrityksien arvoa tehostamalla näiden operatiivista toimintaa. Tuoreempi tutkimus ei kuitenkaan johdonmukaisesti tue näitä löydöksiä. Vaikka aiheesta on olemassa huomattava määrä epäjohdonmukaisia tutkimustuloksia, ei käyttöpääoman hallintaa tutkimustulosten takana ole juurikaan analysoitu. Tämä on selkeä puute aiemmassa tutkimuksessa, sillä yhtiön toimintaa voidaan tehostaa vapauttamalla käyttöpääomaan sitoutunutta pääomaa, etenkin käyttöpääomaintensiivisillä toimialoilla. Tämä tutkimus tukee aikaisempaa empiiristä tutkimusta analysoimalla kohdeyhtiöiden operatiivisen kannattavuuden ja tuottavuuden tunnuslukuja. Lisäksi tutkimus tuottaa uutta tietoa kohdeyhtiöiden käyttöpääoman hallinnasta yritysostojen jälkeisen tarkasteluajanjakson aikana. Suomessa toimialan tutkimusta on johtanut Suomen Pääomasijoitusyhdistys ry, joka käyttää tutkimuksissaan lähteinä pääomasijoitustietokantoja, joiden dataa yhdistyksellä ei ole oikeutta jakaa. Yhdistys alkoi kuitenkin vuonna 2013 tekemään julkisista lähteistä kerättyä listaa pääomasijoitusyhtiöiden tekemistä sijoituksista, joka toimitettiin tämän tutkimuksen tekijälle. Tässä tutkimuksessa käsitellään 84 suomalaista pääomasijoituksen saanutta kohdeyritystä ja näiden tunnuslukujen muutosta vuosien 2014 ja 2019 välillä. Kohdeyrityksien muutosta tunnusluvuissa verrataan samalla toimialalla toimivien verrokkiyrityksien tunnuslukuihin, jonka avulla selvitetään pääomasijoituksen vaikutus yrityksen operatiiviseen toimintaan, sekä poistetaan nousu- ja laskusuhdanteiden rooli tutkimustuloksien taustalla. Tutkimus osoittaa kohdeyrityksien kasvavan liikevaihdollisesti ja työntekijämääriltään selvästi nopeammin kuin heidän verrokkinsa. Tutkimus ei tue aikaisempaa näyttöä pääomasijoittajien kyvystä kasvattaa kohdeyrityksien operatiivista kannattavuutta. Vaikka operatiivinen kannattavuus ei ole keskimäärin noussut, pääomasijoittajat ovat pystyneet tehostamaan kohdeyhtiöiden käyttöpääoman tehokkuutta tarkasteluajanjakson aikana. Tätä ei olla saavutettu lisäämällä ostovelkojen määrää tai lyhentämällä varastojen kiertoaikaa, vaan pääsääntöisesti lyhentämällä myyntisaamisten kiertoaikaa. Tutkimus ei kuitenkaan löydä tilastollista riippuvuutta tehostuneen käyttöpääoman ja yrityksen operatiivisen kannattavuuden välillä. Tutkimuksen mukaan tärkein tekijä kohdeyrityksien operatiivisen kannattavuuden kasvun taustalla on ollut henkilöstön tuottavuuden tehostuminen, jota seurattiin vertaamalla yrityksien henkilöstökustannuksien suhdetta yrityksen myynteihin.
Keywords: profitability; working capital; venture capital; productivity; private equity investors; enterprises; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management